Answer:
5
Step-by-step explanation:
3+5+7+8+9+4+2+1+3+8=50
50/10=5
Answer:
Statements:
m<b = 180 - m<a
m<c = 180 - m<d
m<b = m<c
180 - m<a = 180 - m<d
Reasons:
The measure of m<b is the angle of a straight line subtracted with m<a. The measure of m<c is the angle of a straight line subtracted with m<d. If m<a and m<d are equal, m<b and m<c are equal.
Step-by-step explanation:
We know, m<a = m<d
So, we need to prove m< b = m<c
Let's start by defining what b and c is
m<b + m<a = 180 This is because a straight line is 180 degrees
m<b = 180 - m<a
m<c + m<d = 180
m<c = 180 - m<d
With this, we can substitute in proof
m<b = m< c
180 - m<a = 180 - m<d
180 - m<a = 180 - m<a
Your welcome for the answer. Tell me if you have any questions in the comments section of this answer! If you could mark this answer as the brainliest, I would greatly appreciate it!
5.75 kid wold be in a row round it
Answer:
(5, - 9)
Step-by-step explanation:
Given
f(x) = (x - 8)(x - 2) ← in factored form
Find the zeros by equating f(x) to zero, that is
(x - 8)(x - 2) = 0
Equate each factor to zero and solve for x
x - 8 = 0 ⇒ x = 8
x - 2 = 0 ⇒ x = 2
The vertex lies on the axis of symmetry which is located at the midpoint of the zeros, hence
=
= 5
Substitute x = 5 into f(x) for corresponding y- coordinate
f(5) = (5 - 8)(5 - 2) = (- 3)(3) = - 9
vertex = (5, - 9)
My possible answers right now are 4 and 2